Desempenho agronômico e produtivo de cultivares de soja em diferentes ciclos e safras - Lemos, Leandro Borges [UNESP]; Farinelli, Rogério; Cavariani, Cláudio [UNESP]; Zapparoli, Rodolfo Alexandre [UNESP] (My University, 2011)
With the objective of gathering technical data about soybean cultivars performance in Botucatu, state of São Paulo, Brazil, an experiment was conducted to evaluate seventeen genotypes. The experiment was conducted during the Summer seasons of 2002/03, 2003/04, and 2004/05. The experiment was set in the field according to a complete block design with four repetitions. The soybean cultivars were ‘Embrapa 48’, ‘BRS 132’. ‘BRS 183’, ‘BRS 212’, ‘IAC 22’, and ‘IAC 23’ (early cycled varieties), ‘BRS 133’, ‘BRS 154’, ‘BRS 156’, ‘BRS 184’, ‘BRS 214’, ‘IAC 18’, and ‘IAC 24’ ( semi early varieties), and ‘BRS 134’, ‘BRS 215’, ‘IAC 8.2’, and ‘IAC 19’ (medium cycled varieties ). All the varieties, during the three cropping years, showed adequate plant height and first pod height of insertion for mechanical harvest. Among the production components, mass of 100 grains showed the highest variability. Cultivar ‘BRS 154’ (medium cycle) showed the highest variation in mass of 100 grains and was also the highest yielding variety in the cropping year of 2004/05. The majority of the cultivars yielded above 3,000 kg ha -1 during the cropping years of 2002/03 and 2004/05. The best yielding performance during the three cropping years were displayed by cultivars ‘IAC 22’ (early cycle), ‘BRS 133’ and ‘BRS 156’ ( both semi early cycled varieties).

Visando a obter informações técnicas para a escolha correta da cultivar de soja, foi desenvolvido um trabalho com o objetivo de avaliar o desempenho agronômico e produtivo de dezessete cultivares de soja nas safras de verão de 2002/2003, 2003/2004 e 2004/2005, em Botucatu (SP). Adotou-se o delineamento experimental em blocos ao acaso, com quatro repetições. As cultivares de soja utilizadas foram: Embrapa 48, BRS 132, BRS 183, BRS 212, IAC 22 e IAC 23 (ciclo precoce); BRS 133, BRS 154, BRS 156, BRS 184, BRS 214, IAC 18 e IAC 24 (ciclo semiprecoce); BRS 134, BRS 215, IAC 8.2 e IAC 19 (ciclo médio). As cultivares de soja semeadas nas três safras apresentam valores para altura de planta e de inserção da primeira vagem satisfatórios para a colheita mecanizada. Dentre os componentes da produção, a massa de 100 grãos obteve a maior variação significativa, destacandose a cultivar BRS 154 (ciclo semiprecoce), obtendo também o valor mais elevado para a produtividade de grãos na safra de 2004/2005. A maioria das cultivares obteve produtividade de grãos acima de 3.000 kg ha -1 nas safras de 2002/2003 e 2004/2005, porém destacam-se nas três safras agrícolas a IAC 22 (ciclo precoce), BRS 133 e BRS 156 (ambas de ciclo semiprecoce).
Agronomic performance of soybean cultivars in different harvests
Keywords: Seasons; Pods per plant; Grains per pod; Grain yield; Glycine max; Vagens por planta; Grãos por vagem; Anos agrícolas; Produtividade de grãos